CH4 Separation from Coal Bed Methane by Hydrate in the SDS and THF Solution. (3rd February 2016) - Zhao, Jianzhong; Zhao, Yangsheng; Liang, Weiguo
Abstract : Hydrate-based separation experiments on simulate coal bed methane gas have been conducted in THF solution and SDS solution. In this work, a novel hydrate-based gas separation process was used to enhance CH4 separation from a 65.7% CH4 /20.2% N2 /O2 gas mixture in the presence of 300 ppm SDS and 19% THF solution. The characteristics of the CH4 separation efficiency, fluctuation of temperature, and pressure were studied at different promoter solution. It was found that hydrate formation was induced by promoter in the solution and occurred immediately as the experiments were started. THF performed better than SDS for CH4 separation from the CH4 /N2 /O2 gas mixture. In particular, the separation coefficients of CH4 and N2 were compared in two solutions. The gas mixture S.Fr. or CH4 recovery is increased from 1.056 to 1.259 while SF of N2 is decreased from 1.183 to 0.634 in THF solution.